2013
DOI: 10.1186/1471-2377-13-16
|View full text |Cite
|
Sign up to set email alerts
|

Mental comorbidity and multiple sclerosis: validating administrative data to support population-based surveillance

Abstract: BackgroundWhile mental comorbidity is considered common in multiple sclerosis (MS), its impact is poorly defined; methods are needed to support studies of mental comorbidity. We validated and applied administrative case definitions for any mental comorbidities in MS.MethodsUsing administrative health data we identified persons with MS and a matched general population cohort. Administrative case definitions for any mental comorbidity, any mood disorder, depression, anxiety, bipolar disorder and schizophrenia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 29 publications
4
159
1
5
Order By: Relevance
“…We limited our selection of physical conditions to those with a validated algorithm that could identify them from administrative data (Marrie et al. 2012, 2013a,b,c). Validated algorithms (Marrie et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We limited our selection of physical conditions to those with a validated algorithm that could identify them from administrative data (Marrie et al. 2012, 2013a,b,c). Validated algorithms (Marrie et al.…”
Section: Methodsmentioning
confidence: 99%
“…Validated algorithms (Marrie et al. 2012, 2013a,b,c) were applied to identify depression, anxiety disorders, and bipolar disorder, as well as chronic lung disease, diabetes, epilepsy, fibromyalgia, hyperlipidemia, hypertension, IBD, and IHD. Because all physical comorbidities were chronic conditions, once an individual met the case definition for a condition, they were considered affected thereafter if alive and residing in Alberta.…”
Section: Methodsmentioning
confidence: 99%
“…However, we have found in previous studies of MS that our findings regarding the relative risk of psychiatric comorbidity after MS diagnosis and temporal trends are consistent across other Canadian provinces (Marrie et al 2015b). Administrative data are not collected for research, but we have validated our approaches to identifying IBD, MS, RA and psychiatric comorbidity using these data (Bernstein et al 1999;Marrie et al 2010;Marrie et al 2013;Marrie et al 2016). These data only capture individuals who have sought care through hospitals or physician visits and do not capture individuals with psychiatric disorders diagnosed by non-physician mental health providers, nor those who have not sought any treatment, although this would affect individuals with and without IMID.…”
Section: Discussionmentioning
confidence: 99%
“…Using case definitions developed and validated in MS and IBD populations (Marrie et al 2013;Marrie et al 2016), we identified individuals in each cohort with depression, anxiety disorder, bipolar disorder, schizophrenia and any psychiatric disorder (51 of depression, anxiety disorder, bipolar disorder, schizophrenia) (Supplementary Table S1). For each psychiatric disorder, we assigned the diagnosis date as the date of first health claim for that disorder.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…18 Although IRB approval was not necessary, it was received on September 4, 2015, from the Cleveland Clinic IRB.…”
Section: Comorbidity In Msmentioning
confidence: 99%